On The Issue Of Teaching Courses “Materials Science” And “Materials Science And Technology Of Structural Materials” - Choriyeva, D.N. (Journal of Higher Education and Academic Advancement, 2024)
In this article you can see role of the disciplines «Engineering materials» and «Materials and pro¬cesses in manufacturing» in the learning programmer of engineers. Materials, especially their properties and selection, are very important practical problem that is why it is necessary to learn diagnostic and analyze materials, computers model materials, the structure and destroying of materials.